Which Factors Are Associated with Local Control and Survival of Patients with Localized Pelvic Ewing's Sarcoma? A Retrospective Analysis of Data from the Euro-EWING99 Trial. Issue 2 (February 2020) - Andreou, Dimosthenis; Ranft, Andreas; Gosheger, Georg; Timmermann, Beate; Ladenstein, Ruth; Hartmann, Wolfgang; Bauer, Sebastian; Baumhoer, Daniel; van den Berg, Henk; Dijkstra, P.D. Sander; Dürr, Hans Roland; Gelderblom, Hans; et al.
Abstract: Background: Local treatment of pelvic Ewing's sarcoma may be challenging, and intergroup studies have focused on improving systemic treatments rather than prospectively evaluating aspects of local tumor control. The Euro-EWING99 trial provided a substantial number of patients with localized pelvic tumors treated with the same chemotherapy protocol. Because local control included surgical resection, radiation therapy, or a combination of both, we wanted to investigate local control and survival with respect to the local modality in this study cohort. Questions/purposes: (1) Do patients with localized sacral tumors have a lower risk of local recurrence and higher survival compared with patients with localized tumors of the innominate bones? (2) Is the local treatment modality associated with local control and survival in patients with sacral and nonsacral tumors? (3) Which local tumor- and treatment-related factors, such as response to neoadjuvant chemotherapy, institution where the biopsy was performed, and surgical complications, are associated with local recurrence and patient survival in nonsacral tumors? (4) Which factors, such as persistent extraosseous tumor growth after chemotherapy or extent of bony resection, are independently associated with overall survival in patients with bone tumors undergoing surgical treatment? Methods: Between 1998 and 2009, 1411 patients with previously untreated, histologically confirmed Ewing's sarcoma were registered in the German Society for Pediatric Oncology and Hematology Ewing's sarcoma database and treated in the Euro-EWING99 trial. In all, 24% (339 of 1411) of these patients presented with a pelvic primary sarcoma, 47% (159 of 339) of which had macroscopic metastases at diagnosis and were excluded from this analysis. The data from the remaining 180 patients were reviewed retrospectively, based on follow-up data as of July 2016. The median (range) follow-up was 54 months (5 to 191) for all patients and 84 months (11 to 191) for surviving patients. The study endpoints were overall survival, local recurrence and event-free survival probability, which were calculated with the Kaplan-Meier method and compared using the log-rank test. Hazard ratios (HRs) with their respective 95% CIs were estimated in a multivariate Cox regression model. Results: Sacral tumors were associated with a reduced probability of local recurrence (12% [95% CI 1 to 22] versus 28% [95% CI 20 to 36] at 5 years, p = 0.032), a higher event-free survival probability (66% [95% CI 51 to 81] versus 50% [95% CI 41 to 58] at 5 years, p = 0.026) and a higher overall survival probability (72% [95% CI 57 to 87] versus 56% [95% CI 47 to 64] at 5 years, p = 0.025) compared with nonsacral tumors. With the numbers available, we found no differences between patients with sacral tumors who underwent definitive radiotherapy and those who underwent combined surgery and radiotherapy in terms of local recurrence (17% [95% CI 0 to 34] versus 0% [95% CI 0 to 20] at 5 years, p = 0.125) and overall survival probability (73% [95% CI 52 to 94] versus 78% [95% CI 56 to 99] at 5 years, p = 0.764). In nonsacral tumors, combined local treatment was associated with a lower local recurrence probability (14% [95% CI 5 to 23] versus 33% [95% CI 19 to 47] at 5 years, p = 0.015) and a higher overall survival probability (72% [95% CI 61 to 83] versus 47% [95% CI 33 to 62] at 5 years, p = 0.024) compared with surgery alone. Even in a subgroup of patients with wide surgical margins and a good histologic response to induction treatment, the combined local treatment was associated with a higher overall survival probability (87% [95% CI 74 to 100] versus 51% [95% CI 33 to 69] at 5 years, p = 0.009), compared with surgery alone. A poor histologic response to induction chemotherapy in nonsacral tumors (39% [95% CI 19 to 59] versus 64% [95% CI 52 to 76] at 5 years, p = 0.014) and the development of surgical complications after tumor resection (35% [95% CI 11 to 59] versus 68% [95% CI 58 to 78] at 5 years, p = 0.004) were associated with a lower overall survival probability in nonsacral tumors, while a tumor biopsy performed at the same institution where the tumor resection was performed was associated with lower local recurrence probability (14% [95% CI 4 to 24] versus 32% [95% CI 16 to 48] at 5 years, p = 0.035), respectively. In patients with bone tumors who underwent surgical treatment, we found that after controlling for tumor localization in the pelvis, tumor volume, and surgical margin status, patients who did not undergo complete (defined as a Type I/II resection for iliac bone tumors, a Type II/III resection for pubic bone and ischium tumors and a Type I/II/III resection for tumors involving the acetabulum, according to the Enneking classification) removal of the affected bone (HR 5.04 [95% CI 2.07 to 12.24]; p < 0.001), patients with a poor histologic response to induction chemotherapy (HR 3.72 [95% CI 1.51 to 9.21]; p = 0.004), and patients who did not receive additional radiotherapy (HR 4.34 [95% CI 1.71 to 11.05]; p = 0.002) had a higher risk of death. The analysis suggested that the same might be the case in patients with a persistent extraosseous tumor extension after induction chemotherapy (HR 4.61 [95% CI 1.03 to 20.67]; p = 0.046), although the wide CIs pointing at a possible sparse-data bias precluded any definitive conclusions. Conclusion: Patients with sacral Ewing's sarcoma appear to have a lower probability for local recurrence and a higher overall survival probability compared with patients with tumors of the innominate bones. Our results seem to support a recent recommendation of the Scandinavian Sarcoma Group to locally treat most sacral Ewing's sarcomas with definitive radiotherapy. Combined surgical resection and radiotherapy appear to be associated with a higher overall survival probability in nonsacral tumors compared with surgery alone, even in patients with a wide resection and a good histologic response to neoadjuvant chemotherapy. Complete removal of the involved bone, as defined above, in patients with nonsacral tumors may be associated with a decreased likelihood of local recurrence and improved overall survival. Persistent extraosseous tumor growth after induction treatment in patients with nonsacral bone tumors undergoing surgical treatment might be an important indicator of poorer overall survival probability, but the possibility of sparse-data bias in our cohort means that this factor should first be validated in future studies. Level of Evidence: Level III, therapeutic study.